Association of Age Shock Index with Mortality among Trauma Patients in the Emergency Department: Association of Age Shock Index with Mortality - Zehra, Areej; Khan, Inayat Ali; Khan, Muhammad; Shaikh, Shahid Pervez; Rathore, Padma; Irfan, Ghazal (Pakistan Journal of Health Sciences, 2025)
Trauma injuries cause significant global morbidity and mortality. While current scoring systems like ISS and TRISS are complex, the Age Shock Index (ASI) offers a simpler, potentially more effective method for estimating patient outcomes. Objective: To evaluate the association of Age Shock Index with 48-hour in-hospital mortality in a trauma population in an Emergency Department (ED). Methods: A comparative cross-sectional study was conducted over eight months in the Emergency Department of Ziauddin University, focusing on pre-selected trauma patients aged 18-65 years. Patients were divided into two groups: the exposed group and non-exposed group, with an Age Shock Index (ASI) ≥ 50, and < 50 respectively. Data analysis was carried out using descriptive statistics, the chi-square test, and independent t-tests with the Statistical Package for Social Sciences (SPSS) version 21.0. Results: Patients with an Age Shock Index (ASI) ≥ 50 had significantly higher 48-hour in-hospital mortality (72%) compared to those with an ASI < 50 (12%) (p < 0.001). The exposed group also received more intravenous fluids, inotropic support, and blood products. No deaths occurred in the emergency room among the exposed group, but a trend towards higher overall mortality was observed (hazard ratio 48.584, 95% CI: 0.511 - 4622.17, p = 0.095). Conclusions: The Age Shock Index (ASI) ≥ 50 is associated with significantly higher 48-hour in-hospital mortality in trauma patients. The exposed group required more intensive interventions, indicating a higher severity of injury. ASI may serve as an effective predictor of patient outcomes in emergency settings.